Integrasi Nilai Karakter Menggunakan Model Value Clarification Technique (VCT) Untuk Mendukung Kurikulum 2013 - Ariyani, Yusinta Dwi; Wahyudi, Andi (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2021)
The 2013 curriculum is currently oriented towards developing student character education. In character education, there are character values ​​that need to be integrated into each subject matter. One way to integrate character values ​​is by using the VCT model. The purpose of this study is to analyze the VCT model in integrating character values ​​in the 2013 curriculum. The method used in this study is a literature study using book sources and articles both national and international journals. The focus of the study in this study is to explain the integration of character values ​​using the VCT model to support the 2013 curriculum. The results show that the VCT model is a highly recommended model for integrating character values. The integration of character values ​​is carried out through clarifying the values ​​related to the conflicts raised in learning. The process of internalizing character values ​​through VCT will be more profound, because students choose the internalized values ​​freely. An important stage of the VCT model is at the stage of providing a stimulus, because at this stage students are expected to understand the problem conflict.